Implementation of Human Capital Management in the Sharia Economist Training (SET) Universitas Sumatera Utara - Putri Adelia; Najla Hanan Fathin; Feronica Simanjorang (TALENTA Publisher, 2024)
This research aims to evaluate and describe the implementation of human capital management through the Sharia Economist Training (SET) event to create human capital management in organizations so that they have high motivation in organizational activities. The focus of the research is on human capital management in the form of Individual Capability, Individual Motivation, Leadership, Organizational Climate and Workgroup Effectiveness. This research is research that uses a qualitative paradigm with descriptive qualitative methods. Data was collected through interviews and participant observations carried out by researchers when holding the SET event. Data was analyzed using SWOT analysis to determine the implementation of human capital management at an event. The research results show that the implementation of human capital management in the SET event can improve skills and performance for growth and development in organizations. USU's SET event has fulfilled several components of human capital management. There are also shortcomings in the publication and documentation division and the Daily Management Body (BPH) division which will later be re-evaluated for the next event. It can be concluded that implementing human capital management in an event is very important for the success and smooth running of the event.